Hydrolysis of goat’s milk casein using gastrointestinal (GI) digestive and gastrointestinal (GI) non-digestive enzymes. - Sukor, Rashidah; Mohd Samsudin, Nurul Izza Nabilah; Muhammad Auwal, Shehu; Mohsin, Aliah Zannierah; Saari, Nazamid (2024)
Casein, a predominant protein in milk, has been identified as an antigen that causes allergic reactions in individuals who consume ruminant milk, particularly those with cow’s milk protein allergy (CMPA). To reduce the triggering response, casein is broken down by enzymes through enzyme hydrolysis. Due to cow’s milk being more industrialised, a study on goat’s milk casein was investigated for the enzyme hydrolysis. This study aims to analyse and compare the degree of hydrolysis and its peptide concentration of goat’s milk casein hydrolysate using trypsin (GI digestive enzyme) and flavourzyme (GI non-digestive enzyme). Hydrolysis was carried out for 0-6 h at their optimal temperature and pH conditions at enzyme-to-substrate (E:S) ratios of 3:1. The enzymes were deactivated at 100 °C for 20 min and the hydrolysates were stored at -20 °C. The degree of hydrolysis and peptide concentration was analysed using o-phthaldialdehyde method and was measured at 340 nm. Results showed that the degree of hydrolysis and peptide concentration increased with time, with flavourzyme exhibiting the highest degree of hydrolysis (76.48 %) and peptide content (2.15 mg/mL).This is due to its high specificity in breaking down the large substrates into smaller components. These findings provide a theoretical foundation to study effect of hydrolysis of goat’ milk casein using different enzymes at their optimal conditions.